Morphological Process Analysis of Morphemes Through Word Formation in New York Times News Articles - Pidia Warahma (Jurnal Syntax Admiration, 2026)
This research aims to analyze the types of word formation and word formation process contained in English articles on New York Times News. This research uses a descriptive qualitative approach. The data collection method was carried out by searching for data on New York Times News related to politics, technology and science articles. Data containing word formation was collected and classified based on its category, then analyzed based on the word formation process. The results of this study show that there are eight types of word formation found in New York Times news articles, namely derivation, inflection, compound, borrowing, clipping, acronym, initialism, and conversion.